International comparative studies: Towards the integration of quantitative and qualitative methods (2013)
International comparative studies are becoming increasingly important in the Social Sciences research field due to the role played by different journalistic cultures within the contemporary society. Researchers cannot understand journalism from the point of view of its internal coherence without doing so in relation to its social context. To understand journalistic culture of a particular country, one must first develop analysis patterns of national contextual. This point is essential in a world where the phenomenon of globalization and convergence is a reality. Therefore, in the field of international comparative research, qualitative and quantitative techniques must be used in order to better understand this. Hence, this article proposes that the comparative perspective of journalistic cultures must come together with the use of qualitative and quantitative methodology because in media studies in general, and in journalism in particular, are the largest producers of meaning.